Reconstructing the Paradigm of Islamic Education: Harmonizing Theocentrism and Anthropocentrism - Ubaidillah Canu; Emha Dzia’ul Haq; Muh. Aldi Ubaidillah (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2025)
Islamic education faces the problem of dualism between the theocentric paradigm oriented towards divinity and the anthropocentric paradigm oriented towards humans. The first paradigm often closes the space for rationality, while the second eliminates spiritual values. This article attempts to reconstruct the paradigm of Islamic education by integrating the values of transcendence and humanity to create a balance between faith and knowledge. Through a qualitative-descriptive approach based on literature studies on the thoughts of al-Attas, al-Faruqi, and Fazlur Rahman, this study emphasizes four main principles of reconstruction: integrative (revelation and reason), humanistic (development of human potential), transformative (formation of social awareness), and contextual (relevant to the times). This reconstructive paradigm is expected to produce perfect human beings who are knowledgeable, faithful, and have noble character and are able to make Islamic education a moral and intellectual force in building civilization.